Palmar purpuric lichen nitidus-clinicopathological and dermoscopic findings - Chun-Yu Cheng; Cheng-Sheng Chiu; Yu-Huei Huang (Wolters Kluwer Medknow Publications, 2013)
Lichen nitidus (LN) is an uncommon dermatosis of unknown etiology. LN confined to the palms is an unusual presentation and only a few cases have been reported. The clinical features may mimic pompholyx, pitted keratosis, and porokeratotic eccrine ostial and dermal duct nevus. We herein report a rare case of palmar purpuric LN with characteristic dermoscopic findings.